The effect of the addition of tomosynthesis to digital mammography on reader recall rate and reader confidence in the UK prevalent screening round. Issue 8 (August 2018) - Upadhyay, N.; Soneji, N.; Stewart, V.; Ralleigh, G.
Abstract : Aim: To compare reader recall rate and confidence associated with recall decisions for digital mammography (DM) alone with DM plus digital breast tomosynthesis (DBT) in the prevalent screening round. Materials and methods: Following regional ethics committee approval and written informed consent from all participating women, DM and DBT were obtained. DM followed by the combination of DM plus DBT were reviewed retrospectively by one of nine radiologists, for 880 women aged between 46 and 53. Differences in recall rates and reader confidence were assessed using the McNemar test and sign test, respectively. Subgroup analyses were performed for conventional prevalent round (aged 50–53 years) and age extension trial (aged 46–49 years) groups, as well as low breast density (BI-RADS A and B) and high breast density (BI-RADS C and D) groups. Results: The recall rate using DM alone was 17.4% (95% confidence interval [CI] 15, 20). The recall rate using DM and DBT was 11.4% (95% CI: 9.5 to 13.8). There was a relative reduction of 35% ( p =0.0001). There were reductions in both the conventional prevalent round (31.1% reduction, p =0.004) and age extension subgroups (37% reduction, p =0.0007). There were also reductions in both the low density group (37.2% reduction, p =0.0007) and the high density group (31.1% reduction, p =0.003). The median confidence rating with the recall decision was 7/10 using DM and 8/10 using the combination of DM and DBT ( p =0.0001). Conclusion: The addition of DBT to DM in the prevalent screening round was found to reduce the reader recall rate, with a modest associated increase in reader confidence. Highlights: Digital breast tomosynthesis (DBT) was a useful adjunct to digital mammography (DM). Adding DBT to DM reduced reader recall rate in the prevalent screening round. There was a reduction in reader recall rate for both low density and high density breast parenchyma. There was a modest associated increase in reader confidence.